영어 듣기 지도 효과에 대한 메타분석 - 맹은경; 김현정 (Studies in English Education, 2022)
Many studies have reported extensively on the effectiveness of listening instruction. However, the reported results have been inconclusive and varied across studies. Synthesizing the results of the quantitative research in this domain, the present study investigates the overall effectiveness of L2 listening instruction (LI) on Korean learners’ listening comprehension. This study also examines how potential variables (i.e., institution, listening approaches, listening types, and activities) affect the effectiveness of LI. For this research, 224 samples from 201 primary studies conducted from 2000 to 2022 were included and coded into CMA software to calculate effect sizes by computing Hedges’s g. The results showed a medium effect of LI (ES=.574) on L2 listening comprehension. The effect of LI was also found to vary according to moderator variables. The effect of LI increased as the school level goes up (Elementary School ES=.480; Secondary School ES=.571; University ES=.838). Findings and pedagogical and research implications are discussed.
Keywords: 메타분석; 듣기 능력; 듣기 지도; 듣기 접근방법; 듣기 유형; 듣기 활동; meta-analysis; listening comprehension; listening instruction; listening approach; listening type; listening activity